Strategies For Building A Golden Generation Through Balanced Nutrition Education For Pregnant Women - Nurul Jannatul Wahidah; Rima Wirenviona; Susanti, Nurul Fatimah; Abadiyah Zakiah Kustantina (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Achieving a golden generation begins with ensuring optimal health and development during the earliest stages of life, particularly through maternal nutrition. This study underscores the critical role of balanced nutrition education for pregnant women in promoting healthy fetal growth and long-term maternal and child well-being. A structured educational intervention was designed to equip pregnant women with comprehensive knowledge on essential nutrients, appropriate meal planning, and the lifelong impact of proper dietary practices. The study engaged 32 pregnant participants and employed a pre- and post-test design to evaluate changes in nutritional knowledge. The results revealed a marked and statistically significant improvement in participants' understanding following the intervention. These findings highlight the effectiveness of targeted, community-based education in enhancing maternal nutritional literacy, thereby contributing to improved pregnancy outcomes and supporting the foundation for a healthier future generation.Keywords: golden generation, balanced nutrition, pregnant women, nutrition education, maternal health.